Pinmap : a multi-touch data visualization to aid perforator vessel selection - Pham, Xuan Phu (2014)
The project addresses the issue of perforator vessel selection in Deep Inferior Epigastric Perforator (DIEP), which is a procedure of reconstructing a breast by using flap tissue surgically extracted from the abdomen. Conventionally, this is a time-consuming process since radiologists need to manually analyze hundreds of raw Computed Tomographic (CT) images to pick a suitable vessel for the operation. The new interface presented in this report is a novel approach that aims to enhance efficiency and quality of selection results by visualizing the human body in 3D space and plotting PinMap, which is a collection of pins with helpful annotation to convey information about vessels. In order to further improve interaction between users and the program, multi-touch technology is applied that enables radiologists to conveniently use finger gestures to explore the 3D volume visualization of the human body and select a vessel candidate. The application is developed in iOS environment using XCode IDE from Apple Inc., and installed in an iPad 3 to employ its multi-touch capabilities. The 3D graphics are implemented with OpenGL ES 2.0 and programmed in Objective-C and C++. The final product is a 3D model of abdomen, including skin, bones, muscles, and vessels. 10 pins are distributed over the map of vessels with different colors and sizes that tell user about the vessel rank and the exploration history. The user explores the 3D volume by rotating with one finger dragging, scaling with 2 fingers, and picking a pin. When selected, the pin displays some information about the vessel location it is pointing to. The project contributes an improvement in DIEP procedure and other areas of clinic surgery. From student’s perspective, it provides great exposure to 3D graphic programming as well as mobile application development.